Search for pair production of scalar leptoquarks decaying into first- or second-generation leptons and top quarks in proton-proton collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Bartels, Falk; Czurylo, Marta; Dunford, Monica; Dittmeier, Sebastian; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; Schöning, André; et al. (The European physical journal. C, Particles and fields, 2021)
A search for pair production of scalar leptoquarks, each decaying into either an electron or a muon and a top quark, is presented. This is the first leptoquark search using ATLAS data to investigate top-philic cross-generational couplings that could provide explanations for recently observed anomalies in B meson decays. This analysis targets high leptoquark masses which cause the decay products of each resultant top quark to be contained within a single high-$$p_{T}$$large-radius jet. The full Run 2 dataset is exploited, consisting of $$139~\hbox {fb}^{-1}$$of data collected from proton-proton collisions at $$\sqrt{s}=13~TeV$$from 2015 to 2018 with the ATLAS detector at the CERN Large Hadron Collider. In the absence of any significant deviation from the background expectation, lower limits on the leptoquark masses are set at $$1480~GeV$$and $$1470~GeV$$for the electron and muon channel, respectively.
ATLAS Collaboration: G. Aad, F. Bartels, M.M. Czurylo, S.J. Dittmeier, M. Dunford, S. Franchino, M. Klassen, A. Krishnan, T. Mkrtchyan, P.S. Ott, D.F.Rassloff, A. Schoening, H-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, X. Yue [und viele weitere]
Gesehen am 23.06.2021